ANALISIS PERBANDINGAN DATA INFORMASI PESAWAT YANG DITERIMA OLEH APLIKASI RTL-SDR 1090 DAN ADS-B THALES AX680 DI PERUM LPPNPI CABANG DENPASAR - RAHMAN, AMIN (Journal of Engineering and Transportation, 2023)
ABSTRACT: Automatic Dependent Surveillance Broadcast (ADS-B) is a surveillance technology using position information from satellites that is broadcast (broadcast) continuously. One of the problems in the development of surveillance technology is how to detect or monitor aircraft with cheap equipment technology, where it is known that surveillance equipment at Indonesian airports tends to be expensive, even the equipment modules for each surveillance tool are sold specifically according to each brand and type. surveillance equipment. The problem also faced at Indonesian airports is the limited surveillance equipment available at each airport, especially ADS-B equipment, where on average branch and unit airports in Indonesia do not yet have ADS-B equipment. Therefore, the author made an analysis, especially of the power received by an ADS-B receiver device that uses RTL-SDR RTL2832U to process signals emitted by aircraft transponders to obtain information in the form of ICAO aircraft address, aircraft callsign, altitude and speed so that it can help users to observe a target or aircraft. Keywords: ADS-B, RTL1090, RTL-SDR RTL2832U